Fluorescence Parameters Measured Concurrently with Net Photosynthesis to Investigate Chloroplastic CO2 Concentration in Leaves of Quercus ilex L. (Journal of Plant Physiology, 1990)
Summary The relationship between net carbon assimilation and non-photochemical quenching (qN) was studied in Q. ilex. In leaf discs, in saturating C02 at various irradiances, qN responded linearly in a 1:1 relationship to 1-A/Ap, which represents the proportion of light energy that is not used in photosynthesis. In calculating Ap, a measured, maximal quantum yield for CO2 fixation of 0.080 for 1-year-oldleaves and 0.085 for young leaveswas used. In attached leaves, under natural conditions, this 1: 1 relation was found when a quantum yield of 0.020 and 0.031 was adopted respectively. According to a model of leaf photosynthesis these quantum yields correspond to stromal CO2 concentrations of 90 and 120μLL L-1, in contrast to an average value of substomatal CO2 concentration of 280μLL L-1 found through gas exchange measurements. Similar results were obtained when the relative increase of fluorescence, observed after a saturating flash given during steady photosynthesis at different irradiances, was plotted against the quantum yield of CO2 fixation. The slope of this relation in attached leaves differed from the slope obtained in saturating CO2 in the leaf discs to such an extent as to indicate stromal CO2 concentrations slightly lower compared with the above values obtained by using qE. The marked difference between stromal and substomatal CO2 concentration could be explained by the highly sclerophyllous character of Q. ilex leaves.